2023
DOI: 10.3390/vaccines11030512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Influenza Vaccination and Associated Factors among Pregnant Women: A Cross-Sectional Study in Korea

Abstract: Pregnant women are vulnerable to developing influenza complications. Influenza vaccination during pregnancy is crucial to avoid infection. The COVID-19 pandemic might exacerbate fear and anxiety in pregnant women. The purpose of this study was to evaluate the effect of the COVID-19 pandemic on influenza vaccination and determine the factors associated with influenza vaccine acceptance among pregnant women in Korea. We conducted a cross-sectional study using an online survey in Korea. A survey questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(78 reference statements)
0
1
1
Order By: Relevance
“…In a previously mentioned study conducted in Korea, receiving a SARS-CoV-2 vaccine was significantly associated with accepting influenza vaccine among pregnant women. Nevertheless, the majority of participants who had a history of influenza vaccination reported that the COVID-19 pandemic did not affect their acceptance of the influenza vaccine or increase its importance [12]. Interestingly, in our study, there was also an evident correlation between COVID-19 and influenza vaccine uptake during pregnancy.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In a previously mentioned study conducted in Korea, receiving a SARS-CoV-2 vaccine was significantly associated with accepting influenza vaccine among pregnant women. Nevertheless, the majority of participants who had a history of influenza vaccination reported that the COVID-19 pandemic did not affect their acceptance of the influenza vaccine or increase its importance [12]. Interestingly, in our study, there was also an evident correlation between COVID-19 and influenza vaccine uptake during pregnancy.…”
Section: Discussioncontrasting
confidence: 50%
“…Factors associated with influenza vaccine acceptance were knowledge of the influenza vaccine and trust in healthcare providers. The results emphasize the importance of providing adequate education to pregnant women in order to enhance their awareness about vaccination [12].…”
Section: Discussionmentioning
confidence: 81%